ANALYSIS OF THE IMPLEMENTATION OF EMKM FINANCIAL ACCOUNTING STANDARDS IN THE PREPARATION OF FINANCIAL REPORTS ON MSMEs, MICRO, SMALL AND MEDIUM ENTITIES (CASE STUDY OF STRAWBERRY DELIGHT IN CIREBON CITY) - Kokoh Nopangga; Surono Surono; Endah Nurhawaeny K; Fitriya Sari; Taufik Aziz (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Analysis of the Implementation of EMKM Financial Accounting Standards in Preparing Financial Statements for MSMEs (Case Study of Strawberry Delight in Cirebon City). Essay. This study aims : (1) to determine the implementation of MSME financial reporting in accordance with SAK EMKM. (2) This is to determine how to prepare MSME financial reports in the context of Implementing SAK EMKM. (2) To find out the obstacles faced by MSME actors and provide solutions in the context of implementing SAK EMKM. The correct accounting cycle has not been implemented by MSME management. This research is a qualitative research using nterview and documentation data collection techniques. The results of this study indicate that Strawberry Delight has not implemented the preparation of financial statements in accordance with SAK EMKM. Management's ignorance of SAK-EMKM is required in preparing the financial statements of the entities they manage or the businesses they operate. Keywords: Application of SAK EMK; Preparation of Financial Report ; SAK EMKM Standards